2023
DOI: 10.3390/cancers15174344
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Lung Cancer Screening: The Future Is Now

Michaela Cellina,
Laura Maria Cacioppa,
Maurizio Cè
et al.

Abstract: Lung cancer has one of the worst morbidity and fatality rates of any malignant tumour. Most lung cancers are discovered in the middle and late stages of the disease, when treatment choices are limited, and patients’ survival rate is low. The aim of lung cancer screening is the identification of lung malignancies in the early stage of the disease, when more options for effective treatments are available, to improve the patients’ outcomes. The desire to improve the efficacy and efficiency of clinical care contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 183 publications
0
3
0
Order By: Relevance
“…6,7 Currently, LDCT is the only internationally recognized screening method that has demonstrated a decrease in mortality rates in high-risk populations for LC. 8 The NLST found that 26.8% of participants had lung nodules larger than 4 mm. 9 Pulmonary nodules are clinically relevant as they can be the initial manifestation of LC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Currently, LDCT is the only internationally recognized screening method that has demonstrated a decrease in mortality rates in high-risk populations for LC. 8 The NLST found that 26.8% of participants had lung nodules larger than 4 mm. 9 Pulmonary nodules are clinically relevant as they can be the initial manifestation of LC.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Lung Screening Trial (NLST) in the US and the Dutch–Belgian Randomized Lung Cancer Screening Trial (NELSON) in Europe, screening with LDCT reduces LC mortality 6,7 . Currently, LDCT is the only internationally recognized screening method that has demonstrated a decrease in mortality rates in high‐risk populations for LC 8 . The NLST found that 26.8% of participants had lung nodules larger than 4 mm 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their adaptability, efforts are still being made to enhance CNN architectures to enable them to manage a diverse array of nodule kinds, sizes, and complexity. Early detection programmes could be revolutionised by CNN integration with computer-aided diagnostic systems, which would also give medical practitioners reliable diagnostic tools quickly and accurately [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thresholding, Atlas, and Region Growing are some examples of classic automatic segmentation methods. These approaches use the shallow qualities of an image, such as grayscale, texture, gradient, and many more, to segment the object [5]. However, conventional segmentation techniques have difficulty distinguishing between tumours and surrounding healthy tissue because their intensity distributions are similar.…”
Section: Introductionmentioning
confidence: 99%